Lipid Cell and Micropapillary Variants of Urothelial Carcinoma of the Ureter - Yu Miyama (Case Reports in Oncology, 2015)
We report on a case of urothelial carcinoma (UC) with lipid cell and micropapillary variants in the ureter. A 64-year-old man presented with gross hematuria. Urinary cytology revealed the presence of atypical urothelial cells. Computed tomography and drip infusion/retrograde pyelography identified a mass-occupying lesion in the left mid-ureter, as well as left hydronephrosis. A clinical diagnosis of left ureteral cancer was given and the patient underwent left nephroureterectomy. Microscopically, the major component of the tumor was a conventional high-grade UC. In the invasive region, however, lipid cell and micropapillary variants of UC were also observed. Upon immunohistochemical analysis, all of the components were diffusely positive for cytokeratin 7 and p53. Intense membranous expression of human epidermal growth factor receptor 2 (HER2) was also observed in both the lipid cell and micropapillary variants of UC, whereas weak and incomplete staining was observed in most regions of the conventional UC. The pathological stage was pT3 N2. Multiple times, the patient experienced recurrence of the UC in the urinary bladder and urethra. Although the patient underwent total cystectomy and urethrectomy, 52 months following the initial surgery, signs of local recurrence developed, as well as multiple lymph node and bone metastases. The patient died 75 months following the initial surgery. To the best of our knowledge, this is the first reported case of a lipid cell variant of ureteral UC. The overexpression of HER2 may be associated with both the lipid cell and micropapillary variants of UC.